Nanovesicle‐Mediated Targeted Delivery of Immune Checkpoint Blockades to Potentiate Therapeutic Efficacy and Prevent Side Effects. Issue 9 (25th January 2022) - Jung, Mungyo; Kang, Mikyung; Kim, Byung‐Seok; Hong, Jihye; Kim, Cheesue; Koh, Choong‐Hyun; Choi, Garam; Chung, Yeonseok; Kim, Byung‐Soo
Abstract: Despite the clinically proven efficacies of immune checkpoint blockades, including anti‐cytotoxic T lymphocyte‐associated protein 4 antibody (αCTLA‐4), the low response rate and immune‐related adverse events (irAEs) in cancer patients represent major drawbacks of the therapy. These drawbacks of αCTLA‐4 therapy are mainly due to the suboptimal activation of tumor‐specific cytotoxic T lymphocytes (CTLs) and the systemic nonspecific activation of T cells. To overcome such drawbacks, αCTLA‐4 is delivered by dendritic cell‐derived nanovesicles presenting tumor antigens (DCNV‐TAs) that exclusively interact with tumor‐specific T cells, leading to selective activation of tumor‐specific CTLs. Compared to conventional αCTLA‐4 therapy, treatment with αCTLA‐4‐conjugated DCNV‐TAs significantly inhibits tumor growth and reduces irAEs in syngeneic tumor‐bearing mice. This study demonstrates that the spatiotemporal presentation of both αCTLA‐4 and tumor antigens enables selective activation of tumor‐specific T cells and potentiates the antitumor efficacy of αCTLA‐4 without inducing systemic irAEs. Abstract : Anti‐cytotoxic T lymphocyte‐associated protein 4 antibody (αCTLA‐4)‐conjugated and tumor antigen (TA)‐loaded nanovesicles derived from dendritic cells can facilitate spatiotemporal delivery of TA and αCTLA‐4 to tumor‐specific T cells. This leads to selective activation of tumor‐reactive T cells, effective inhibition of tumor growth and prevention of immune‐related adverse events, improving the current immune checkpoint blockade therapies.